Economic, technological, environmental, and infrastructural problems of the development of the Republic of Tuva and adjacent territories: results of the IV International Scientific and Practical conference - Soyan, Sonchalai Ch. (The New Research of Tuva, 2024)
On October 19–20, 2023, the IV International Scientific and Practical Conference “Regional Economy: Technologies, Economics, Ecology and Infrastructure” took place in Kyzyl, Russia, at the Tuvinian Institute for Complex Development of Natural Resources of the Siberian Branch of the Russian Academy of Sciences. The conference discussed the results of ongoing research into economic, technological, environmental, and infrastructure issues related to the development of the Republic of Tuva and neighboring regions. The research topics covered the main areas presented in the reports in the following sections: “Formation of a long-term socio-economic strategy for the region”, “Geology and mineral resource potential of Tuva and adjacent territories”, “Modern mathematical, geo-informational and remote methods for analyzing, processing and displaying natural and anthropogenic processes”, “Rational management of nature and environmental protection”, and “Innovative technologies as a factor in the development of modern society”. The review presents abstracts from a number of important reports.